PARIS - Møhl, Perle (Tidsskriftet Antropologi, 2003)
Unique, and yet a résumé of all of France, so massively dense that it draws everything in like a black hole. Parisian navigations, various forms of transportation, giving very different perceptions and perspectives, maplike, tourlike, and in between. Nostalgia, nothing is like it was – and it never has been. Still keeping contact, from afar, through the generous don of water, flowing to its underground from a small rich village.